Biosensors for the detection of flaviviruses: A review - Ana-Belén Blázquez; Nereida Jiménez de Oya (Synthetic and Systems Biotechnology)
Flaviviruses affect the lives of millions of people in endemic regions and also have the potential to impact non-endemic areas. Factors such as climate change, global warming, deforestation, and increased travel and trade are linked to the spread of flaviviruses into new habitats and host species. Given the absence of specific treatments and the limited availability of vaccines, it is imperative to understand the biology of flaviviruses and develop rapid and sensitive diagnostic tests. These measures are essential for preventing the transmission of these potentially life-threatening pathogens. Flavivirus infections are mainly diagnosed using conventional methods. However, these techniques present several drawbacks, including high expenses, time-consuming procedures, and the need for skilled professionals. The search for fast, easy-to-use, and affordable alternative techniques as a feasible solution for developing countries is leading to the search for new methods in the diagnosis of flaviviruses, such as biosensors.This review provides a comprehensive overview of different biosensor detection strategies for flaviviruses and describes recent advances in diagnostic technologies. Finally, we explore their future prospects and potential applications in pathogen detection. This review serves as a valuable resource to understand advances in ongoing research into new biosensor-based diagnostic methods for flaviviruses.